The individual systematic difference between CoaguChek and STA-SPA+ - Åsberg, Arne; Hegseth, Hilde; Averina, Maria; Løfblad, Lena (Scandinavian journal of clinical and laboratory investigation, 2019)
Using CoaguChek to measure PT-INR and comparing the results with those from the hospital laboratory, some patients get consistent results while others do not. The extent of this problem is unknown. Our study aimed to quantify the between-subject variation of the systematic PT-INR difference between CoaguChek and a hospital laboratory method. We used register data with PT-INR results from both CoaguChek and a hospital laboratory method (STA-SPA+) in samples taken simultaneously from 108 patients. After excluding five patients with outlying results, we used mixed-effects models to estimate individual slopes and intercepts to describe the systematic relationship between the two methods for each patient, and calculated the fraction of patients having a systematic difference greater than 0.3 INR units. The included 103 patients had from 3 to 16, median seven data pairs measured over a time span from 15 to 2319, median 234 days. The mean of individual slopes was 1.113, with a standard deviation of 0.137. Corresponding values for the intercept were -0.151 and 0.208, respectively. Adjusted for the average systematic difference, the proportion of patients with a systematic difference greater than 0.3 INR units increased from 15% at a PT-INR level of 2.5 to 50% at a PT-INR level of 4. The systematic difference between CoaguChek and STA-SPA + varies considerably between patients. This precludes using a single, common formula to make the CoaguChek results directly comparable to the results from the hospital laboratory.